Effect of blending and emulsification on thermal behavior, solid fat content and microstructure properties of palm oil based margarine fats. - Saadi , Sami; Ariffin, Abdul Azis; Mohd Ghazali, Hasanah; Mat Sahri, Miskandar; Mohammed, Abdulkarim Sabo; Boo, Huey Chern (Wiley-Blackwell, 2011)
The ability of palm oil (PO) to crystallize as beta prime polymorph has made it an attractive option for the production of margarine fat (MF). Palm stearin (PS) expresses similar crystallization behavior and is considered one of the best substitutes of hydrogenated oils due to its capability to impart the required level of plasticity and body to the finished product. Normally, PS is blended with PO to reduce the melting point at body temperature (37 °C). Lipid phase, formulated by PO and PS in different ratios were subjected to an emulsification process and the following analyses were done: triacylglycerols, solid fat content (SFC), and thermal behavior. In addition, the microstructure properties, including size and number of crystals, were determined for experimental MFs (EMFs) and commercial MFs (CMFs). Results showed that blending and emulsification at PS levels over 40 wt% significantly changed the physicochemical and microstructure properties of EMF as compared to CMF, resulting in a desirable dipalmitoyl-oleoyl-glycerol content of less than 36.1%. SFC at 37 °C, crystal size, crystal number, crystallization, and melting enthalpies (ΔH) were 15%, 5.37 μm, 1425 crystal/μm2, 17.25 J/g, and 57.69J/g, respectively. All data reported indicate that the formation of granular crystals in MFs was dominated by high-melting triacylglycerol namely dipalmitoyl-oleoyl-glycerol, while the small dose of monoacylglycerol that is used as emulsifier slowed crystallization rate.Practical Application: Most of the past studies were focused on thermal behavior of edible oils and some blends of oils and fats. The crystallization of oils and fats are well documented but there is scarce information concerning some mechanism related to crystallization and emulsification. Therefore, this study will help to gather information on the behavior of emulsifier on crystallization regime; also the dominating TAG responsible for primary granular crystal formations, as well as to determine the best level of stearin to impart the required microstructure properties and body to the finished products.